Effects of upper extremity blood flow restriction training on muscle strength and hypertrophy: a systematic review and meta-analysis - Jing, Jiapeng; Zheng, Qinzhi; Dong, Hongfei; Wang, Yan; Wang, Peiji; Fan, Di; Xu, Zhuo (Frontiers in Physiology, 2025)
BackgroundLow load resistance training with blood flow restriction (LL-BFRT) has been shown to improve muscle strength and hypertrophic function. The effect of LL-BFRT on lower extremity muscle improvement has been widely discussed. However, no studies have discussed the effect of this training method on the upper extremity muscles until now. This systematic review and meta-analysis focused on the use of LL-BFRT in the upper extremity muscles.MethodsThe relevant literature was searched in four major databases including Pubmed, Web of science, the Cochrane Library and Embase from 10 June 2024. The Cochrane Collaboration’s tool and GRADE methodology were used to assess the risk of bias and quality in included studies.ResultsThe meta-analysis included a total of 11 articles with 220 participants. LL-BFRT and high load resistance training (HLRT) produced similar effects in improving upper extremity muscle strength (low certainty evidence, SMD: −0.35; 95%CI: −0.73 to 0.03; p: 0.07; I2: 2%) and hypertrophy (moderate certainty evidence, SMD: −0.36; 95%CI: −0.73 to 0.01; p: 0.05; I2: 0%). Compared with low load resistance training (LLRT), LL-BFRT showed greater advantages in improving upper extremity muscle strength (low certainty evidence, SMD: 0.67; 95%CI: 0.33 to 1.01; p: 0.0001; I2: 0%) and hypertrophy (low certainty evidence, SMD: 0.37; 95%CI: 0.06 to 0.67; p: 0.02; I2: 0%).ConclusionIn general, LL-BFRT can be used as an alternative training method for HLRT to improve upper extremity muscle strength and hypertrophy. Our study shows that the effect of LL-BFRT on upper extremity muscle is limited by age and region. It is necessary to formulate reasonable exercise programs according to the characteristics of different demographic groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024555514.